Nodulation of white clover inoculated whith two Rhizobium trifolii strains under different Al and Mn levels in nutrient solution - Brose, Edemar; Schaffarth, Edoard (Pesquisa Agropecuaria Brasileira, 2014)
A trial in nutrient solution was carried out with clover and two Rhizobium trifolii strains on pH 4.6 with six levels of Al (0, 25, 50, 75, 100 and 125 μM) and two levels of Mn (10 and 200 μM). The main objective was to identify the critic level of Al to select the Al tolerant and eliminate the Al susceptible strains. The rhizobia strains used were EEL 8382 (Al susceptible) and EEL 13882 (Al tolerant). The critic level of Al on the tolerant strain EEL 13882 was 50 μM in base of plant nodulation and dry matter production on both levels of Mn. The susceptible strain EEL 8382 was inhibited with 25 μM of Al at 10 μM of Mn, whereas on 200 μM of Mn the Ai was toxic at 50 μM. On the range of 0 to 50 μM of Al it did not affect significantly the root elongation, thus the effect of Al on the plant nodulation is attributed as a more direct effect on the rhizobia sensitivity than on the plant root. A possible interaction between Al and Mn is discussed.